Remuneration structure by occupation in the Kuyavian-Pomeranian Voivodeship (Economic and Political Thought, 2018)
The article aims to assess the differences in the level of remuneration andidentify factors that influence this differentiation in the Kuyavian-PomeranianVoivodeship in the period of 2007–2016. The analysis covers the differencesin remuneration in different occupational groups. The average gross monthlyremuneration in the voidodeship, standard deviations in the region and therelation between the average remuneration and the dynamics of increaseare used. Based on the data, statistical data such as the average, standarddeviations and the variation index are calculated. Statistical data publishedin the 2007–2016 Statistical Yearbooks of the Statistical Office in Bydgoszczare used for the analysis and assessment.
Keywords: remuneration, pay, occupations, employee